جدلية اللغة والمجاز عند القاضي البيضاوي - رحال, هشام (Université de M'sila, 2018)
أخذت لغة الق آ رن الكريم بألباب من سمعوه، وألفوا ألفاظه، وعلت الأصوات بتلاوته، وشنفت الأسماع بكلماته وحلو بيانه، ووقف علماء المسلمين يفسّرون ما غمض من ألفاظه ومعانيه، ويضعون في ذلك المؤلّفات اللغوية، وهذا باعتباره مبتدأ كثير من النّظريات اللغوية والبلاغية التي ارتبطت بتفسير ه، مما أثّر في طبيعة الدّرس اللغوي على نحو عام، وأعطاه طابعه الخاص الذي يرجع في جذوره الأولى إلى البحث في أصول اللغة والبيان المتعلّق بالبلاغة، لذلك جاء بحثنا ليميط اللّثام عن جدلية اللغة والبلاغة المتمثلة في المجاز، محاولين الوقوف في تفسير البيضاوي على بعض النّماذج التي عالج فيها الرّجل الآيات القرآنية من منطلق تأويلي.
The scholars of the Muslims interpreted the ambiguity of his words and meanings, and put in that linguistic literature, and this as a beginner many of the linguistic and rhetorical theories that have been associated with his interpretation, which is the language of the Holy Quran with the words of the people who heard him, and the words of his words, Influenced the nature of the language lesson in general, and gave it its own character, which is rooted in the first roots to research the origins of the language and the statement on rhetoric, so our research came to reveal the dialectic language and eloquence in the metaphor, trying to stand in the interpretation of albaydawi on some models Treat the man out of the Koranic verses explanatory.
Keywords: اللغة، المجاز، النصّ القرآني، التأويل.( language, metaphor, Quranic text, interpretation )